The synchronization of a fractional order hyperchaotic system based on passive control - 吴朝俊 张彦斌 杨宁宁 (Chinese physics B, 2011)
This paper investigates the synchronization of a fractional order hyperchaotic system using passive control. A passive controller is designed, based on the properties of a passive system. Then the synchronization between two fractional order hyperchaotic systems under different initial conditions is realized, on the basis of the stability theorem for fractional order systems. Numerical simulations and circuitry simulations are presented to verify the analytical results.